The time traveler's guide to Regency Britain a handbook for visitors to 1789-1830 - Mortimer, Ian 1967- (Pegasus Books, 2022)
"A vivid and immersive history of Georgian England that gives its reader a firsthand experience of life as it was truly lived during the era of Jane Austen, Percy Bysshe Shelley, and the Duke of Wellington. This is the age of Jane Austen and the Romantic poets; the paintings of John Constable and the gardens of Humphry Repton; the sartorial elegance of Beau Brummell and the poetic license of Lord Byron; Britain's military triumphs at Trafalgar and Waterloo; the threat of revolution and the Peterloo massacre. In the latest volume of his celebrated series of Time Traveler's Guides, Ian Mortimer turns to what is arguably the most-loved period in British history: the Regency, or Georgian England. A time of exuberance, thrills, frills and unchecked bad behavior, it was perhaps the last age of true freedom before the arrival of the stifling world of Victorian morality. At the same time, it was a period of transition that reflected unprecedented social, economic, and political change. And like all periods in history, it was an age of many contradictions--where Beethoven's thundering Fifth Symphony could premier in the same year that saw Jane Austen craft the delicate sensitivities of Persuasion. Once more, Ian Mortimer takes us on a thrilling journey to the past, revealing what people ate, drank, and wore; where they shopped and how they amused themselves; what they believed in, and what they feared. Conveying the sights, sounds, and smells of the Regency period, this is history at its most exciting, physical, visceral--the past not as something to be studied but as lived experience."--
Keywords: Geschichte 1789-1830; Alltag; Großbritannien; Great Britain / History / 1789-1820; Great Britain / History / Regency, 1811-1820; Great Britain / History / George IV, 1820-1830; Great Britain / Social life and customs / 19th century; Grande-Bretagne / Histoire / 1789-1820; Grande-Bretagne / Histoire / 1811-1820 (Régence); Grande-Bretagne / Histoire / 1820-1830 (George IV); Grande-Bretagne / Murs et coutumes / 19e siècle; Manners and customs; Great Britain; 1789-1899; History; Informational works